2006
DOI: 10.1110/ps.062098206
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing functional production of G protein‐coupled receptors in Pichia pastoris to levels required for structural studies via a single expression screen

Abstract: We have optimized the expression level of 20 mammalian G protein-coupled receptors (GPCRs) in the methylotrophic yeast Pichia pastoris. We found that altering expression parameters, including growth temperature, and supplementation of the culture medium with specific GPCR ligands, histidine, and DMSO increased the amount of functional receptor, as assessed by ligand binding, by more than eightfold over standard expression conditions. Unexpectedly, we found that the overall amount of GPCR proteins expressed, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
119
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 46 publications
6
119
0
Order By: Relevance
“…This is the first report of a fusion phytase gene in P. pastoris which has been shown to be suitable for high-level expression of various heterologous proteins, either intracellular or secretory. Under fermentation conditions P. pastoris has been shown to be able to grow to high cell densities capable of giving high levels of expressed protein with levels greater than 10 g/L reported (Cregg and Higginns, 1995;Romanos, 1995;André et al, 2006). So there is a huge potential for the fermentation of fusion phytase if optimizing the cultivation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of a fusion phytase gene in P. pastoris which has been shown to be suitable for high-level expression of various heterologous proteins, either intracellular or secretory. Under fermentation conditions P. pastoris has been shown to be able to grow to high cell densities capable of giving high levels of expressed protein with levels greater than 10 g/L reported (Cregg and Higginns, 1995;Romanos, 1995;André et al, 2006). So there is a huge potential for the fermentation of fusion phytase if optimizing the cultivation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Note that, for the initial optimization, we recommend adding either DMSO or His, as we find that the presence of these chemical chaperones can afford an additional 30% improvement to the whole-cell expression levels 6 . Until now it was unclear as to why these chemical chaperones can improve membrane protein production levels 20 .…”
mentioning
confidence: 99%
“…Using Steps 20-23, one can also test other culture conditions that have shown to be successful to improve membrane protein production, for example, the addition of a ligand to the culture medium 20 , or to switch the culture to 20 °C after galactose induction. However, in the latter case, we have found that only 5% of the targets we have tested give an additional improvement in expression compared with standard growth at 30 °C (ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the limited amount of RNA obtained from an individual cell, it cannot be excluded that -due to the technical limitations of single-cell expression analysis -very low abundance transcripts remain undetected, in particular if the RNA quality is compromised. Since GPCRs are, in many cases, expressed at very low levels (43), it is in this context important to consider the sensitivity of the detection system used for single-cell expression analysis. A recent study directly compared the 2 major readout systems for single-cell expression analysis, RT-PCR and RNA sequencing (RNA-Seq), with respect to their sensitivity for GPCR detection in murine aortic smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%